Potential of Green Solvent as a Polyphenolic and Antioxidant Extraction Medium in Brown Seaweed Sargassum Cristaefolium - Laili Syarifah; Jihan Novitasari; Elsa Yuliana; Maylina Ilhami Khurniyati; Pinctada Putri Pamungkas (SINTA Journal (Science, Technology, and Agricultural), 2026)
This study aims to evaluate the effectiveness of water-based environmentally friendly solvents in extracting polyphenol compounds and determine the antioxidant activity of brown seaweed Sargassum cristaefolium. The method used was a quantitative experiment with various types of solvents (aquadest, tap water, and mineral water), temperatures (40°C, 55°C, 70°C), and extraction times (20, 40, 60 minutes). The parameters analyzed included total phenols, total flavonoids, and antioxidant activity using the DPPH method. The results showed that the type of solvent and extraction conditions significantly influenced the release of bioactive compounds. The highest antioxidant activity (79.40%) was obtained from mineral water at 40°C for 60 minutes. The highest phenol content (2.42 mg GAE/g) was also found in mineral water at 70°C, while the highest flavonoid content (4595.42 µg QE/g) was produced by aquadest at 70°C for 60 minutes. In general, increasing extraction temperature and time increases the content of bioactive compounds to a certain limit before thermal degradation occurs. The presence of minerals such as Ca²⁺, Mg²⁺, and HCO₃⁻ in mineral water is thought to increase the stability and solubility of compounds. Thus, water-based solvents have the potential to be a safe and environmentally friendly alternative to organic solvents in the food and healthcare industries.